Psychological Well-Being dalam Tasawuf: Studi Pemikiran Haji Abdul Malik Karim Amrullah (HAMKA) - Muhammad Hisyam (Universitas Islam Negeri Raden Intan Lampung, 2026)
Abstract; Psychological well-being (PWB) has become a central issue in modern society, which is experiencing an increase in mental disorders due to the absence of values ​​and the loss of traditional life guidance. This study examines the concept of well-being from a Sufi perspective through the thoughts of Haji Abdul Malik Karim Amrullah (Hamka), a renowned Indonesian cleric and intellectual. The research was conducted qualitatively and descriptively, employing a literature study approach, with Hamka's three main works on Sufism serving as primary sources. The analysis was conducted by adopting Carol D. Ryff's Psychological Well-being (PWB) model, which comprises six dimensions: self-acceptance, positive relationships with others, autonomy, environmental mastery, life purpose, and personal growth. The results of the study show that Hamka's Sufi thoughts are not only relevant to the dimensions of modern Positive Well-being (PWB) but also offer a synthesis between Islamic spiritual values and the psychological needs of contemporary humans. These findings emphasise the importance of integrating religious and psychological approaches in building human well-being as a whole, especially in the context of Islam and Indonesia. Keywords: Hamka's Thoughts; Modern Sufism; Psychological Well-Being. Abstrak; Kesejahteraan psikologis (psychological well-being/PWB) menjadi isu sentral di tengah masyarakat modern yang mengalami peningkatan gangguan mental akibat kekosongan nilai dan hilangnya panduan hidup tradisional. Studi ini menelusuri konsep well-being dalam perspektif tasawuf melalui pemikiran Haji Abdul Malik Karim Amrullah (Hamka), seorang ulama dan intelektual besar Indonesia. Penelitian dilakukan secara kualitatif-deskriptif dengan pendekatan studi pustaka, menggunakan tiga karya utama Hamka tentang tasawuf sebagai sumber primer. Analisis dilakukan dengan mengadopsi model PWB Carol D. Ryff yang meliputi enam dimensi: penerimaan diri, hubungan positif dengan orang lain, otonomi, penguasaan lingkungan, tujuan hidup, dan pertumbuhan pribadi. Hasil penelitian menunjukkan bahwa pemikiran tasawuf Hamka tidak hanya relevan dengan dimensi-dimensi PWB modern, tetapi juga menawarkan sintesis antara nilai-nilai spiritual Islam dan kebutuhan psikologis manusia kontemporer. Temuan ini menegaskan pentingnya integrasi pendekatan religius dan psikologis dalam membangun kesejahteraan manusia secara utuh, khususnya dalam konteks keislaman dan keindonesiaan. Kata Kunci: Pemikiran Hamka; Psycological Well-Being; Tasawuf Modern